Meningkatkan Aktivitas Keterampilan Menulis Dalam Bentuk Poop Up Book Mel Menggunakan Model Project Based Learning Kombinasi Cooperative Integrated Reading And Composition Dan Talking Stick - Widyaningsih Lilik Tri; Mahmuddin Mahmuddin (CV. ITTC INDONESIA, 2024)
An obstacle in research is the lack of quality writing activities from students, which has a negative impact on achieving their learning outcomes in Indonesian language subjects. The reasons behind this are because learning only flows from one direction, the focus in learning Indonesian is on grammar, and there is a lack of use of various models in learning. This research applies the Classroom Action Research (PTK) methodology by holding 4 meeting sessions. The data used is quality data, obtained through observations of teacher activities, student activities, and student writing abilities. These findings show that teachers have good quality in learning activities at the initial stage of meetings I-III, getting the title